SERTIPIKAT ELEKTRONIK DALAM PERSPEKTIF PERLINDUNGAN DATA PRIBADI - Shabranah, Andi Nur; Maskun, Maskun; Aswan, Muhammad (Universitas Ekasakti, 2023)
This article aims to examine the form of personal data protection in electronic certificates. This is a normative research with statutory and conceptual approaches. At the beginning of 2021, the Regulation of the Agrarian Affairs Ministry/Head of the National Land Agency concerning Electronic Certificates (it is referred to as Ministerial Regulation of National Land Agency Number 1 of 2021) which was issued on January 12, 2021 to modernize the land handling and services. This modernization is a form of digital transformation of the Ministry of Agrarian Affairs and Spatial Planning of National Land Agency (BPN). The digital transformation which is carried out by The Agrarian Affairs Ministry includes improving digital services and processing personal data from manual to digital, transforming conventional certificates into electronic certificates. The massive data leaks has become public concern regarding personal data. The Law number 27 of 2022 concerning the Protection of Personal Data, it can guarantee the rights of citizens by providing protection for personal data. The result of the research shows a product issued by the government with processing personal data. Based on the PDP Law, it must obtain approval from the Personal Data Protection Officer as a personal data protection form of the land rights holders.